Analisis Stabilitas Lereng dengan Perkuatan Bronjong Menggunakan Metode Kesetimbangan Batas (Studi Kasus: Ruas Jalan Batas Kab. Muna-Kab. Buton Utara) - Anafi Minmahddun (Jurusan Teknik Sipil, Universitas Halu Oleo, 2024)
The challenge in road infrastructure development is the potential for slope instability due to topographic conditions, as observed in a road segment in Southeast Sulawesi Province. This study aims to analyze slope stability using gabion reinforcement. A topographic survey and soil investigation using the cone penetration test were conducted to determine the topographic conditions and soil layers to ensure that the landslide mitigation design meets the required criteria. The analysis was performed using the limit equilibrium method to determine the overall slope safety factor, and an internal stability analysis was also conducted to assess the safety of the gabions against potential shear failure, overturning, and bearing capacity failure. The results of the analysis showed that the safety factors for the gabions against shear, overturning, and bearing capacity were 3.33, 11.44, and 5.49, respectively. Furthermore, the global slope stability analysis using the Spencer method obtained a safety factor of 1.70. All the safety factor values meet the required safety factor criteria.